Activation of Mitogen-activated Protein Kinase (Mitogen-activated Protein Kinase/Extracellular Signal-regulated Kinase) Cascade by Aldosterone - Hendron, Eunan (The American Society for Cell Biology, 2002)
Aldosterone in some tissues increases expression of the mRNA encoding the small monomeric G protein Ki-RasA. Renal A6 epithelial cells were used to determine whether induction of Ki-ras leads to concomitant increases in the total as well as active levels of Ki-RasA and whether this then leads to subsequent activation of its effector mitogen-activated protein kinase (MAPK/extracellular signal-regulated kinase) cascade. The molecular basis and cellular consequences of this action were specifically investigated. We identified the intron 1-exon 1 region (rasI/E1) of the mouse Ki-ras gene as sufficient to reconstitute aldosterone responsiveness to a heterologous promotor. Aldosterone increased reporter gene activity containing rasI/E1 threefold. Aldosterone increased the absolute and GTP-bound levels of Ki-RasA by a similar extent, suggesting that activation resulted from mass action and not effects on GTP binding/hydrolysis rates. Aldosterone significantly increased Ki-RasA and MAPK activity as early as 15 min with activation peaking by 2 h and waning after 4 h. Inhibitors of transcription, translation, and a glucocorticoid receptor antagonist attenuated MAPK signaling. Similarly, rasI/E1-driven luciferase expression was sensitive to glucocorticoid receptor blockade. Overexpression of dominant-negative RasN17, addition of antisense Ki-rasA and inhibition of mitogen-activated protein kinase kinase also attenuated steroid-dependent increases in MAPK signaling. Thus, activation of MAPK by aldosterone is dependent, in part, on a genomic mechanism involving induction of Ki-ras transcription and subsequent activation of its downstream effectors. This genomic mechanism has a distinct time course from activation by traditional mitogens, such as serum, which affect the GTP-binding state and not absolute levels of Ras. The result of such a genomic mechanism is that peak activation of the MAPK cascade by adrenal corticosteroids is delayed but prolonged.